Right Minithoraсotomy as a Standard Approach for Mitral Valve Surgery - Babliak, O. D.; Demianenko, V. M.; Babliak, D. Y.; Marchenko, A. I.; Revenko, K. A.; Pidgaina, L. V. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Background. Minimally invasive mitral valve surgery provides many advantages for patients. The aim. To investigate and represent our own experience in minimally invasive mitral valve surgery, and to describe the operative technique. Materials and methods. The study was included 100 consecutive patients who underwent a minimally invasive mitral valve repair or replacement through the right lateral minithoracotomy from June 2017 to December 2019. Results. Mitral valve repair was performed in 87 patients (87%), and 13 patients (13%) were required mitral valve replacement. In 24 patients (24%), concomitant procedures were performed: tricuspid valve repair, atrial septal defect repair and left atrial myxomectomy. Ring anuloplasty was performed in all patients who underwent mitral valve repair. Additional methods of correction were used in accordance to the lesion anatomy: neochords implantation, cleft and leaflet perforation closure, leaflet resection, Alfieri (edge-to-edge) stitch, posterior leaflet plication. There was no in-hospital and 30-day mortality. Post-operative strokes were not reported. No wound complications were observed in the femoral cannulation area. The total length of stay in a hospital was 6 ± 1.46 (3–9) days. There were no cases of mitral valve insufficiency greater more than mild degree after mitral valve repair at the time of discharge. Conclusions. Minimally invasive mitral valve surgery can be performed as a routine standard approach, provides safe and effective correction of the mitral valve defects, allows excellent results of mitral valve repair and replacement in various abnormalities. Minimally invasive approach enables to perform a large number of reconstructive valve techniques and perform simultaneous correction of atrial septal defects, tricuspid valve repair and atrial neoplasm removal.